The Effect of the Makassar Tidak Rantasa (MTR) Policy on Environmental Cleanliness in Makassar City - Inrinofita Sari; Suswanta Suswanta; Nuryanti Mustari (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
This study aims to prove the research hypothesis regarding the Effect of Makassar Tidak Rantasa (MTR) Policy on Environmental Cleanliness in Makassar City. Measurement of Environmental Hygiene Variables is Communication, Resources, Bureaucratic Structure and Implementation. In this study researchers used quantitative descriptive methods with data sources from questionnaires through google form with 100 respondents, and data processing was carried out using SEM-PLS. The results showed that the R-Square value was 0.902. it can be concluded that the interpretation of Environmental Hygiene is 0.902%, where the R-Square structural model is identified in the strong / good category. Variables to measure the MTR Policy on Environmental Cleanliness are Implementation, Communication, Bureaucratic Sources, Resources. The four variables have a positive and significant effect on the MTR Policy on Environmental Cleanliness, which means that it is accepted with a P value of 0.000, 0.000, 0.039 and 0.035.